Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes

J'aime à toi : esquisse d'une félicité dans l'histoire - Irigaray, Luce (Grasset, 1992)
Qui es-tu, toi qui n'es, ne seras jamais moi ni mien ? Je t'écoute comme la révélation d'une vérité irréductible à moi. Tu m'as saluée, reconnue. Tu interroges tes limites. Je te donne du silence où le futur de toi - et peut-être de moi avec toi - peut émerger et se fonder. Je ne m'approche pas immédiatement de toi. Je ne te connaîtrai jamais de manière absolue. Je laisse de l'air, de l'espace, du mystère autour de nous. Éveillée à toi, recueillie, j'invente des paroles qui te touchent de leur souffle sans t'enlever à toi. Cet abord intransitif cherche aide auprès de l'univers, de la beauté, de la sagesse, de l'Histoire. En cette uvre déjà, j'aime à toi. Puisse ce " à " garder l'intention entre nous encore et toujours vive, berceau de l'être que notre transcendance l'un à l'autre enfante. " Après une critique de la maîtrise de notre culture par le genre masculin et la définition de médiations nécessaires à la constitution du sujet féminin, Luce Irigaray élabore ici une dialectique de l'intersubjectivité fondée sur la différence sexuelle. J'aime à toi marque donc un nouveau temps dans l'ouvre de la philosophe, le premier ayant été ouvert par Speculum, De l'autre femme.
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

La nature humaine est deux - Irigaray, Luce (J'aime à toi : esquisse d'une félicité dans l'histoire, 1992)
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

"Chapitre I".De l'assujettissement des femmes. - Mill, John Stuart (De l'assujettissement des femmes, 1992)
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

De l'assujettissement des femmes. - Mill, John Stuart (Arenes, 1992)
L´écrivain britannique John Stuart Mill était l´un des premiers écrivains masculins à se positionner pour l´égalité des sexes et à défendre la libération des femmes. Il se pencha sur la liberté économique des femmes et était de l´avis que le rôle d´une femme dans le mariage devait évoluer. Le livre « De l’assujettissement des femmes » est un classique de la littérature féministe. Le philosophe et politicien britannique John Stuart Mill (1806+1873) est un des penseurs libéraux les plus importants du 19e siècle. Il est particulièrement connu pour ses théories d´utilitarisme. Il s´est occupé de divers sujets politiques et philosophiques, dont les concepts de liberté et d´égalité des sexes.
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; phi4336; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles